Real-time Data Visualization of Inventory Lending Services using Metabase: A Case Study - Ida Bagus Gede Anandita; Ni Putu Anggi Karolina; I Made Dwi Putra Asana (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2026)
Effective inventory management is critical in higher education but is often constrained by rigid reporting mechanisms. At the Institut Bisnis dan Teknologi Indonesia (INSTIKI), substantial asset volumes are currently presented in static tabular formats, resulting in suboptimal information availability. This impedes the Bureau of General Affairs from extracting rapid strategic insights regarding asset conditions and maintenance. This study addresses these inefficiencies by developing a real-time data visualization system utilizing Metabase as an open-source Business Intelligence (BI) tool. The system integrates directly with operational databases to transform raw data into interactive visual insights without complex ETL processes. The implementation yielded 14 comprehensive dashboard menus, covering metrics such as asset distribution, depreciation analysis, lending trends, and infrastructure quality control. User Acceptance Testing (UAT) indicated a 96% approval rate within the